2017 External Sector Report. (Policy Papers; Policy Paper ;, 2017)
Global current account imbalances were broadly unchanged in 2016, with minor shifts adding to the reconfiguration under way since 2013. The fall in commodity prices, uneven cyclical recoveries in systemic economies, and differences in policy responses contributed to the rotation of imbalances. Current account surpluses of oil-exporting economies, as a group, shifted from large surpluses to small deficits, while deficits in emerging and developing economies narrowed markedly. At the same time, surpluses and deficits in key advanced economies widened. These trends were generally supported by real exchange rate movements. Overall excess current account imbalances (i.e., deficits or surpluses that deviate from desirable levels) represented about one-third of total global imbalances in 2016, remaining broadly unchanged since 2013, although increasingly concentrated in advanced economies. In particular, excess imbalances narrowed in emerging and developing economies, led by a smaller excess surplus in China and smaller excess deficits in others (Brazil, Indonesia, South Africa, Turkey). This narrowing, however, was accompanied by a widening of excess imbalances in some advanced economies. The persistence of large excess surpluses in several advanced economies (e.g. Germany, Korea, the Netherlands, Singapore, Sweden) remains a distinguishing feature of the constellation of imbalances, an issue that is explored in greater detail in this year's report. Persistent global excess imbalances suggest that automatic adjustment mechanisms are weak. While the rotation of excess imbalances toward advanced economies-with deficits increasingly concentrated in the United States and United Kingdom-likely entails lower deficit-financing risks in the near term, the increased concentration of deficits in a few economies carries greater risks of disruptive trade policy actions. Diverging stock positions coupled with continued overreliance on demand from debtor countries could also pose risks to global growth and raise the likelihood of disruptive adjustments down the road. With nearly-closed output gaps in most systemic economies, addressing external imbalances in a growth-friendly fashion requires a recalibration of the policy mix in deficit and surplus economies alike. Excess deficit countries should move forward with fiscal consolidation, while gradually normalizing monetary policy in tandem with inflation developments. Excess surplus economies with fiscal space should reduce their reliance on easy monetary policy and allow for greater fiscal stimulus. Where monetary policy is constrained from playing a role, as in individual euro area members, fiscal and structural policies to facilitate relative price adjustments should take priority. Meanwhile, structural policies in excess surplus countries should focus on lifting distortions that constrain domestic demand or limit trade competition; while in excess deficit economies, policies should be directed to improving external competitiveness and overall saving. Protectionist and mercantilist policies should be avoided as they are detrimental to global growth.